2018
DOI: 10.1021/acssuschemeng.8b03588
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Application of Microwave Treatment for Recovering of Rare Earth Elements from Phosphogypsum

Abstract: Some rare earth elements (REEs) are classified as strategic materials because of their increasingly high demand, supply uncertainty, and near zero recycling. For tackling the sustainability challenges associated with REEs, their technospheric mining, i.e., recovery from secondary sources, is imperative. Characterization results indicate that phosphogypsum, a byproduct of the fertilizer industry, contains about 0.03− 0.4 wt % REEs. Here, a novel process was developed that utilizes microwave irradiation to enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Therefore, the loss of REEs during the beneficiation process mainly resulted from that portion remaining in the gypsum. Microwave radiation has also been used by Reid et al [49] and Lambert et al [50] for enrichment of PG prior to REE leaching. It was found that microwaving PG resulted in dielectric heating of water molecules present in PG crystals causing the formation of pores in the PG matrix as the water vapour escaped.…”
Section: Beneficiation Methodsmentioning
confidence: 99%
“…Therefore, the loss of REEs during the beneficiation process mainly resulted from that portion remaining in the gypsum. Microwave radiation has also been used by Reid et al [49] and Lambert et al [50] for enrichment of PG prior to REE leaching. It was found that microwaving PG resulted in dielectric heating of water molecules present in PG crystals causing the formation of pores in the PG matrix as the water vapour escaped.…”
Section: Beneficiation Methodsmentioning
confidence: 99%
“…Other countries, such as Spain, India, Brazil, and the United States, have signi cant performance in indicators that re ect the quality of papers. These countries have made many contributions to the research on the properties and utilization of PG (Campos et al, 2017;Lambert et al, 2018;Luis Guerrero et al, 2020;Nayak et al, 2018). Generally speaking, the regions where PG academic papers are produced are distributed all over the world.…”
Section: Technology Life Cycle Theorymentioning
confidence: 99%
“…q e ¼A þ Blnc e (9) where A and B are constants related to adsorption potential and adsorption heat, respectively. Figure 6 shows the adsorption isotherms of zeolite CAN following the Langmuir, Freundlich and Temkin adsorption models, respectively, and Table 3 lists the isotherm parameters obtained by the three adsorption models.…”
Section: Adsorption Performance Of Zeolite Can For Mbmentioning
confidence: 99%
“…Microwave has been found as a rapid, highly selective and thermally efficient heating technique, where the heat comes from the frictional loss caused by the rotation of polarized molecules in the oscillating electromagnetic field. [9] According to the previous literature reports, the microwave heating technique was mainly employed to intensify the hydrothermal process of synthesizing zeolites from activated natural minerals. [10] However, the effect of the microwave-assisted hydrothermal (MH) technique on the activation process of nature minerals is rarely reported.…”
Section: Introductionmentioning
confidence: 99%